Status analysis of quality control of administered infusion solution with cytotoxic drugs - Shan Wang; Feng-Ying Zhang; Xue Dou; Xiao-Lin Pan; Chen Su; Jin-Lei Tian; Dian-Ping Mu (Oncology Reviews)
The administered infusion solution is a sterile preparation that can be used directly for intravenous infusion in patients by mixing one or more intravenous drugs using aseptic operation technology. The pharmacy intravenous admixture service (PIVAS) center is a professional technical service department in hospitals, where the majority of inpatient-administered infusion solutions are prepared. During the processes of dissolution, dilution, preparation, storage, and use of intravenous drugs, the quality control of the administered infusion solution can be affected by various factors. At present, there are no relevant standards or guidance documents for the quality control of administered infusion solutions. Cytotoxic drugs are still the main treatment option for cancer patients and are mainly prepared in PIVAS centers in most hospitals. In this study, we mainly focused on the quality control of cytotoxic drug-administered infusion solutions and explored associated factors (diluent, container, concentration, temperature, and light), physical stability (visual appearance, pH, osmolality, and particulate matter), chemical stability (content), and biological stability (sterility). Most of the studies reviewed in this paper have insufficient data on the related factors and physicochemical stability of the administered infusion solutions. Research on the sterility of administered infusion solutions is particularly limited, with only one article addressing this aspect. Ensuring the quality of cytotoxic drug-administered infusion solutions is vital for the safe administration of drugs to cancer patients, so it is very important to enhance associated research. This article summarized the relevant literature on the quality control of cytotoxic drug-administered infusion solutions and provided a reference for safer and more efficient use of these drugs in clinical practice.